Factors Associated with Presence of Human Papillomavirus Infection among Women: Findings from New Cervical Cancer Screening in Kelantan, Malaysia - Mohd Zin, Nur Dalilah; Tengku Ismail, Tengku Alina; Hashim, Noran (Malaysian Journal of Medicine and Health Sciences, 2023)
Introduction: Human papillomavirus (HPV) infection is known to cause cervical cancer worldwide. Recently, Malaysia introduced HPV DNA detection testing for cervical cancer screening program. However, knowledge regarding factors for HPV infection among women still limited. Thus, this study aimed to determine the prevalence and factors associated with HPV infection among women in Kelantan, a north-eastern state of Malaysia. Methods: This study used secondary data extracted from HPV DNA test registry book and HPV DNA laboratory request forms. Data on all Malaysian women aged 30 to 49 years old in 2019 reported in registry book were included. Simple random sampling was applied. All information from book and forms were collected using proforma and analysed using SPSS. The outcomes were categorised into HPV infection and non-HPV infection. The parameters related to factors associated with HPV infection were determined using multivariable logistic analysis. Results: The prevalence of HPV infection among women attending the new cervical screening was 8.4% (95% CI 6.4%, 10.3%). Those aged between 30 and 39 years old (AdjOR 2.09; 95% CI 1.16, 3.78, p=0.014), had 5 or more parities (AdjOR 2.82; 95% CI 1.58, 5.06, p<0.001) and hormonal contraception users (AdjOR 7.48; 95% CI 4.07, 13.76, p<0.001) were significantly associated with HPV infection. Conclusion: Overall, the prevalence of HPV infection from this study is comparable to the local and international studies. Age, number of parities and hormonal contraception users influence the HPV infection. This finding could help in designing more targeted screening for cervical cancer. References: International Agency for Research on Cancer (IARC). GLOBOCAN 2020: Global cancer burden (Internet. 2020. 2021 Jan 12;. International Agency for Research on Cancer (IARC). The Grants Register 2018. 13 November 2020;:412-3. Ronco G, Dillner J, Elfström K, Tunesi S, Snijders PF, Arbyn M, Kitchener H, Segnan N, Gilham C, Giorgi-Rossi P, Berkhof J, Peto J, Meijer CLM. Efficacy of HPV-based screening for prevention of invasive cervical cancer: follow-up of four European randomised controlled trials. The Lancet. 2014. 9916;383:524-32. Palmer K. IARC Monographs on the Evaluation of Carcinogenic Risks to Humans. Volume 98: Painting, Firefighting and Shiftwork. International Agency for Research on Cancer. Occupational Medicine.61:521-2. Bruni, L., Albero G, Serrano B, Mena M, Gómez D, Muñoz J, et al.. Human Papillomavirus and Related Disease Report:World. https://hpvcentre.net/statistics/reports/XWX.pdf?t=1623905691793. Accessed 2019. Clifford G, Franceschi S, Diaz M, Muñoz N, Villa L. Chapter 3: HPV type-distribution in women with and without cervical neoplastic diseases. Vaccine. 2006 Aug 31;24:S26-S34. Center for Disease Control and Prevention (CDC).. Epidemiology and Prevention of Vaccine-Preventable Disease. 13th. (Elisha Hall, A. , Patricia Wodi, , Jennifer Hamborsky, , Valerie Morelli, , Sarah Schillie, eds).. Bruni L, Albero G, Serrano B, Mena M, Gómez D, Muñoz J. Human Papillomavirus and Related Diseases in Malaysia. HPV Inf Cent (Internet. 2019. 2020 Oct 26;:1-68. Zhang R, Shi T, Ren Y, Lu H, Wei Z, Hou W, Zhang M, Xu C. Risk factors for human papillomavirus infection in Shanghai suburbs: A population-based study with 10,000 women. Journal of Clinical Virology. 2013 Sep 1. 2020 Nov 6;58:144-8. Ribeiro A, Costa M, Alves RF, Villa L, Saddi V, Carneiro MDS, Zeferino L, Rabelo-Santos S. HPV infection and cervical neoplasia: associated risk factors. Infectious Agents and Cancer. 2015 Dec 26. 2020 Oct 23;10:16. Nielsen A, Kjaer S, Munk C, Iftner T. Type-Specific HPV Infection and Multiple HPV Types: Prevalence and Risk Factor Profile in Nearly 12,000 Younger and Older Danish Women. Sexually Transmitted Diseases. 2008 Mar. 2020 Oct 20;35:276-82. Sabeena S, Bhat P, Kamath V, Bhat S, Nair S, N. Community-Based Prevalence of Genital Human Papilloma Virus (HPV) Infection: a Systematic Review and Meta-Analysis. Asian Pac J Cancer Prev. 2017 Jan 1. 2020 Oct 22;18:145-54. Zahnd W, Rodriguez C, Jenkins W. Rural‐Urban Differences in Human Papillomavirus‐associated Cancer Trends and Rates. The Journal of Rural Health. 2019 Mar 28;35:208-15. Mitchell S, Sekikubo M, Biryabarema C, Byamugisha JK, Steinberg M, Jeronimo J, Money D, Christilaw J, Ogilvie G. Factors associated with high-risk HPV positivity in a low-resource setting in sub-Saharan Africa. American Journal of Obstetrics and Gynecology. 2014 Jan. e7;210:81.e1-81.e7. Adnan M, Abdullah J, Md Ibharim L, Wee Hoe T, Janan D, Abdullah N, Idris N, Abdul Wahab A, Othman A, Hashim MA, Md Said N, Adnan R, Yahaya S, Amin N, Mohd Noh M, Sufa'at N, Abdullah R, Yusof Y, Ahmad @mat Reduaan Z, Ahdary N, Annamallai T, Ali F, Kannasamy K, Shukri R, Simadiri T, Sai Wah T, Baharudin NA. Expanding Opportunities for Science, Technology, Engineering and Mathematics Subjects Teaching and Learning: Connecting through Comics. Malaysian Journal of Medical Sciences. 2019. 2020;26:127-33. Chong P, Asyikin N, Rusinahayati M, Halimatun S, Rozita R, Ng C. High prevalence of human papillomavirus DNA detected in cervical swabs from women in southern Selangor, Malaysia. Asian Pac J Cancer Prev. 2010;11:1645-51. Tran LT, Tran L, Bui T, Le DT, Nyitray A, Markham C, Swartz M, Vu-Tran C, Hwang L. Risk factors for high-risk and multi-type Human Papillomavirus infections among women in Ho Chi Minh City, Vietnam: a cross-sectional study. BMC Women's Health. 2015 Dec 21. 2020 Oct 23;15:16. Sukeri S, Idris Z, Zahiruddin W, Shafei M, Idris N, Hamat R, Jamaluddin TT, Osman M, Wahab Z, Daud A. A qualitative exploration of the misconceptions, knowledge gaps and constructs of leptospirosis among rural and urban communities in Malaysia. PLOS ONE. 2018 Jul 18;13:e0200871. Paengchit K, Kietpeerakool C, Lalitwongsa S. Prevalence and Genotype Distribution of HPV among Women Attending a Cervical Cancer Screening Mobile Unit in Lampang, Thailand. Asian Pacific Journal of Cancer Prevention. 2014 Aug 15;15:6151-4. Tay S, Oon LE. Prevalence of cervical human papillomavirus infection in healthy women is related to sexual behaviours and educational level: a cross-sectional study. International Journal of STD & AIDS. 2014 Dec 19. 2020 Oct 23;25:1013-21. Khoo S, Bhoo-Pathy N, Yap S, Anwar Shafii M, Hairizan Nasir N, Belinson J, Subramaniam S, Goh P, Zeng M, Tan H, Gravitt P, Woo Y. Prevalence and sociodemographic correlates of cervicovaginal human papillomavirus (HPV) carriage in a cross-sectional, multiethnic, community-based female Asian population. Sexually Transmitted Infections. 2018 Jun 1. 2020 Oct 17;94:277-83. Ezzah N, Kumar S, Chin V, Falah Y, A. High Prevalence of Human Papillomavirus Types 56 and 70 Identified in the Native Populations of Sabah, Malaysia. Asian Pac J Cancer Prev. 2018 Oct 26. 2020 Oct 16;19:2807-13. Saslow D, Runowicz C, Solomon D, Moscicki A, Smith R, Eyre H, Cohen C. American Cancer Society Guideline for the Early Detection of Cervical Neoplasia and Cancer. CA: A Cancer Journal for Clinicians. 2002 Nov 1;52:342-62. Sauvaget C, Nene B, Jayant K, Kelkar R, Malvi S, Shastri S, Sankaranarayanan R. Prevalence and Determinants of High-Risk Human Papillomavirus Infection in Middle-Aged Indian Women. Sexually Transmitted Diseases. 2011 Oct;38:902-6. Siriaunkgul S, Settakorn J, Sukpan K, Srisomboon J, Suprasert P, Kasatpibal N, Khunamornpong S. Population-based Cervical Cancer Screening Using High-risk HPV DNA Test and Liquid-based Cytology in Northern Thailand. Asian Pacific Journal of Cancer Prevention. 2014 Aug 30;15:6837-42. Li J, Huang R, Schmidt J, Qiao Y. Epidemiological Features of Human Papillomavirus (HPV) Infection among Women Living in Mainland China. Asian Pacific Journal of Cancer Prevention. 2013 Jul 30. 2020 Nov 2;14:4015-23. Manga M, Fowotade A, Abdullahi Y, El-Nafaty A, Adamu D, Pindiga H, Bakare R, Osoba A. Epidemiological patterns of cervical human papillomavirus infection among women presenting for cervical cancer screening in North-Eastern Nigeria. Infectious Agents and Cancer. 2015 Dec 2. 2021 May 30;10:39. Department of Statistic Malaysia (DOSM). . Marriage and divorce Statistic, Malaysia, 2020. Department of Statistic Malaysia (DOSM).. 2020;. Shahramian I, Heidari Z, Mahmoudzadeh-Sagheb H, Moradi A, Forghani F. Prevalence of HPV Infection and High Risk HPV Genotypes (16, 18), among Monogamous and Polygamous Women. 2011. 2021 May 22;40:113-21. Haji R, A. Poligami di Malaysia. J Syariah. 2019;5:167-86. Gargano J, Nisenbaum R, Lee D, Ruffin Iv M, Steinau M, Horowitz I, Flowers L, Tadros T, Birdsong G, Unger E. Age-Group Differences in Human Papillomavirus Types and Cofactors for Cervical Intraepithelial Neoplasia 3 among Women Referred to Colposcopy. Cancer Epidemiology, Biomarkers & Prevention. 2012 Jan. 2020 Oct 30;21:111-21. Lyu Y, Ding L, Gao T, Li Y, Li L, Wang M, Han Y, Wang J. Influencing Factors of High-Risk Human Papillomavirus Infection and DNA Load According to the Severity of Cervical Lesions in Female Coal Mine Workers of China. Journal of Cancer. 2019. 2020 Oct 25;10:5764-9. Kahesa C, Kjaer S, Ngoma T, Mwaiselage J, Dartell M, Iftner T, Rasch V. Risk factors for VIA positivity and determinants of screening attendances in Dar es Salaam, Tanzania. BMC Public Health. 2012 Dec 7. 2020 Oct 30;12:1055. Jensen K, Schmiedel S, Norrild B, Frederiksen K, Iftner T, Kjaer S. Parity as a cofactor for high-grade cervical disease among women with persistent human papillomavirus infection: a 13-year follow-up. British Journal of Cancer. 2013;108:234-9. Sun L, Herkanaidu K, Mohur P, Ramudoo P, J. Effect of Pregnancy on HPV Infection and on its Mode of Management. Med J Obs Gynecol (Internet. 2017. 1099;5. Sc R, Gimenes F, Abreu Alp De, Irie M, Souza R, Santana R. Risk factors for cervical HPV infection and genotypes distribution in HIV-infected South Brazilian women. Infect Agents Cancer. 2014;9. Lee M, Najwa Rosman A, Khan A, Md Haris N, Alyana N, Mustapha S, Sakina Muhamad N, Husaini. Awareness of cervical cancer among women in Malaysia. Int J Health Sci. 2018. 2020 Dec 31;12:42-8. Baskran K, Kumar P, Santha K, Sivakamasundari I. Cofactors and Their Association with Cancer of the Uterine Cervix in Women Infected with High-Risk Human Papillomavirus in South India. Asian Pacific Journal of Cancer Prevention. 2019. 2020 Oct 27;20:3415-9. Roura E, Travier N, Waterboer T, De Sanjosé S, Bosch F, Pawlita M, Pala V, Weiderpass E, Margall N, Dillner J, Gram I, Tjønneland A, Munk C, Palli D, Khaw K, Overvad K, Clavel-Chapelon F, Mesrine S, Fournier A, Fortner R, Ose J, Steffen A, Trichopoulou A, Lagiou P, Orfanos P, Masala G, Tumino R, Sacerdote C, Polidoro S, Mattiello A, Lund E, Peeters P, Bueno-De-Mesquita H, Quirós J, Sánchez M, Navarro C, Barricarte A, Larrañaga N, Ekström J, Lindquist D, Idahl A, Travis R, Merritt M, Gunter M, Rinaldi S, Tommasino M, Franceschi S, Riboli E, Castellsagué X. The Influence of Hormonal Factors on the Risk of Developing Cervical Cancer and Pre-Cancer: Results from the EPIC Cohort. PLOS ONE. 2016 Jan 25;11:e0147029. Catarino R, Vassilakos P, Tebeu P, Schäfer S, Bongoe A, Petignat P. Risk factors associated with human papillomavirus prevalence and cervical neoplasia among Cameroonian women. Cancer Epidemiology. 2016. Feb;40:60-6. Cervical cancer and hormonal contraceptives: collaborative reanalysis of individual data for 16 573 women with cervical cancer and 35 509 women without cervical cancer from 24 epidemiological studies. The Lancet. 2007 Nov. 9599;370:1609-21. Marks M, Gravitt P, Gupta S, Liaw K, Kim E, Tadesse A, Phongnarisorn C, Wootipoom V, Yuenyao P, Vipupinyo C, Rugpao S, Sriplienchan S, Celentano D. The association of hormonal contraceptive use and HPV prevalence. International Journal of Cancer. 2011 Jun 15. 2020 Oct 17;128:2962-70. Volpato L, Siqueira I, Nunes R, Piovezan A. Association between Hormonal Contraception and Injuries Induced by Human Papillomavirus in the Uterine Cervix. Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics. 2018 Apr 27;40:196-202. Sangwa-Lugoma G, Ramanakumar A, Mahmud S, Liaras J, Kayembe P, Tozin R, Lorincz A, Franco E. Prevalence and Determinants of High-Risk Human Papillomavirus Infection in Women From a Sub-Saharan African Community. Sexually Transmitted Diseases. 2010 Dec. 2020 Oct 19;38:308-15. Liu M, He Z, Zhang C, Liu F, Liu Y, Li J, Xu Z, Wang Q, Hang D, Shen N, Pan Y, Guo C, Cai H, Ke Y. Transmission of genital human papillomavirus infection in couples: a population-based cohort study in rural China. Scientific Reports. 2015;5:1-10. Bell S, Bishai D. Unmet Need and Sex: Investigating the Role of Coital Frequency in Fertility Control. Studies in Family Planning. 2017;48:39-53. Averbach S, Ma Y, Smith-Mccune K, Shiboski S, Moscicki A. The effect of intrauterine devices on acquisition and clearance of human papillomavirus. American Journal of Obstetrics and Gynecology. 2017 Apr;216:386.e1-386.e5. Kocturk S, Gul M. Human papillomavirus DNA in premenopausal and postmenopausal women. Obstetrics & Gynecology International Journal. 2020;11:1-5. Asyikin N, A. Prevalence of Human Papilloma virus infection and its associated risk factors among non-cervical cancer women in Selangor, Malaysia (. 2009;. Tadesse S. Socio-economic and cultural vulnerabilities to cervical cancer and challenges faced by patients attending care at Tikur Anbessa Hospital: a cross sectional and qualitative study. BMC Women's Health. 2015 Dec 16;15:75.